Graphene oxide-supported zinc oxide nanoparticles for chloroprene rubber with improved crosslinking network and mechanical properties. (September 2019) - Xu, Zongchao; Zheng, Long; Wen, Shipeng; Liu, Li
Abstract: Obtaining a homogeneous dispersion of graphene in a rubber matrix by efficient melt blending is a great challenge presently faced by the rubber industry. In this study, graphene oxide (GO)-supported zinc oxide (ZG) hybrids were prepared by electrostatic adsorption and in situ growth methods. Subsequently, ZG hybrid/chloroprene rubber (ZG/CR) composites were fabricated by the traditional method of melt blending. The results revealed that the ZnO nanoparticles were adsorbed on the surface of the GO layers. Strong interfacial interactions developed between the ZnO nanoparticles and GO sheets. In ZG/CR composites, the ZG hybrids were homogeneously dispersed in the CR matrix and formed strong interfacial interactions with the latter. The ZG hybrids accelerated the crosslinking rate and increased the crosslinking density of the CR composites. Compared to the ZnO-GO/CR (control) composites, the modulus at 300% elongation, tensile strength, and reinforcing index of the ZG/CR composites increased by 31%, 60%, and 32%, respectively.